Training on making healthy and safe meat processed food in Cileunyi Wetan, Bandung Regency - Putri Widyanti Harlina; Syamsul Huda; Vira Putri Yarlina (Universitas Muhammadiyah Magelang, 2023)
Meat and meat products are an important source of nutrition for humans because they contain several nutrients such as protein, lipids, minerals and vitamins. Most of the women from the PKK team and Posyandu cadres in Cileunyi Wetan Village, Cileunyi District, Bandung Regency work as housewives and do not know enough about making processed meat food that is safe, healthy and halal. Therefore, this community service aims to provide information in the form of counseling and training regarding the manufacture of processed meat food. The program is carried out with lectures, discussions and training in making sausages and shredded meat. The results of the program reveal that partners become more aware of the quality of meat, as well as how to properly store and process meat so that nutrition is maintained. Furthermore, at the end of this program, partners can continue to increase awareness of the importance of quality fresh meat which will be processed into a food source of protein which is important for families and partners can also increase creativity independently in procuring healthy processed food.